Emotional capital and ‘care’ practices in e-learning: a theoretical perspective / Nuramira Anuar - Anuar, Nuramira (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
We are witnessing augmented movements in Higher Education recently- especially in that of online learning and in the case of UiTM, Open Distance Learning (ODL), which has accelerated tremendously. In terms of Higher Education Institutions (HEIs), both educators and learners are experiencing isolation due to physical distancing to help curb the pandemic which results in emotional distress especially in e-learning environment. Many research studies focus on how to best support both the educators and students especially in terms of technology and the use of technology in teaching and learning, but little research studies have delved into the aspects of emotional labour and ‘care’ in e-learning especially during this crisis. In this neoliberal era, this aspect of ‘care’ could sometimes be neglected and failed to be at the forefront in teaching and learning in HEIs. This theoretical paper will discuss Bourdieuian social theory especially emotional capital, and how it relates to online teaching and learning practices in a crisis. It is hoped that by stressing on emotional capital and care in teaching and learning practices, both educators and students could be better supported in e-learning environment during this crisis and beyond.